Menavigasi Inovasi di Era Manufaktur Cerdas: Bagaimana Budaya Organisasi dan Modal Intelektual Memediasi Pengaruh Berbagi Pengetahuan terhadap Perilaku Inovatif - Kusuma Dwi Wikka Kukuh Satrianto; Fudji Sri Mar’ati; Jaya Ramadaey Bangsa; Hardi Utomo (Universitas Ngudi Waluyo, 2026)
The development of the manufacturing industry in the era of smart manufacturing requires stronger knowledge-based innovation capabilities to sustain organizational competitiveness, where innovation is not only determined by the availability of knowledge but also by how knowledge is shared and internalized within the organization. This study aims to examine the effect of knowledge sharing on innovative behavior with intellectual capital and organizational culture as mediating variables among manufacturing employees in Central Java, Indonesia. A quantitative approach was employed using a survey method involving 195 respondents, with data collected through a structured questionnaire based on a 1–5 Likert scale and analyzed using Structural Equation Modeling with Partial Least Squares (PLS-SEM). The results indicate that knowledge sharing has a significant positive effect on intellectual capital, organizational culture, and innovative behavior. Furthermore, intellectual capital and organizational culture are found to significantly mediate the relationship between knowledge sharing and innovative behavior. These findings highlight that strengthening knowledge sharing practices, supported by robust intellectual capital and a conducive organizational culture, is a key driver in enhancing employees’ innovative behavior in the manufacturing sector. Abstrak Perkembangan industri manufaktur di era manufaktur cerdas menuntut peningkatan kemampuan inovasi berbasis pengetahuan untuk menjaga daya saing organisasi, di mana inovasi tidak hanya ditentukan oleh ketersediaan pengetahuan tetapi juga oleh bagaimana pengetahuan tersebut dibagikan dan diinternalisasi dalam organisasi. Penelitian ini bertujuan untuk menganalisis pengaruh knowledge sharing terhadap innovative behavior dengan intellectual capital dan organizational culture sebagai variabel mediasi pada karyawan perusahaan manufaktur di Jawa Tengah, Indonesia. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survei terhadap 195 responden dan pengumpulan data melalui kuesioner berbasis skala Likert 1–5 yang dianalisis menggunakan Structural Equation Modeling berbasis Partial Least Squares (PLS-SEM). Hasil penelitian menunjukkan bahwa knowledge sharing berpengaruh positif dan signifikan terhadap intellectual capital, organizational culture, dan innovative behavior, serta intellectual capital dan organizational culture terbukti memediasi hubungan tersebut secara signifikan. Temuan ini menegaskan bahwa penguatan praktik knowledge sharing yang didukung oleh intellectual capital dan budaya organisasi yang kondusif merupakan faktor kunci dalam meningkatkan perilaku inovatif karyawan di industri manufaktur.